VD_FINDINFO AVS 45/19 - 18/2020 vom 4. Juni 2020 - VD Tribunal cantonal (2020)
DÉCISION DE COTISATIONS, COTISATION AVS/AI/APG, ABSENCE D'ACTIVITÉ LUCRATIVE | 3 LAI, 27 LAPG, 3 al. 1 LAVS, 28 al. 1 RAVS, 28 al. 2 RAVS